Which Cue to “Want?” Central Amygdala Opioid Activation Enhances and Focuses Incentive Salience on a Prepotent Reward Cue - Mahler, Stephen V. (Society for Neuroscience, 2009)
The central nucleus of the amygdala (CeA) helps translate learning into motivation, and here, we show that opioid stimulation of CeA magnifies and focuses learned incentive salience onto a specific reward cue (pavlovian conditioned stimulus, or CS). This motivation enhancement makes that cue more attractive, noticeable, and liable to elicit appetitive and consummatory behaviors. To reveal the focusing of incentive salience, we exploited individual differences in an autoshaping paradigm in which a rat prefers to approach, nibble, and sniff one of two reward-associated stimuli (its prepotent stimulus). The individually prepotent cue is either a predictive CS+ that signals reward (8 s metal lever insertion) or instead the metal cup that delivers sucrose pellets (the reward source). Results indicated that CeA opioid activation by microinjection of the μ agonist DAMGO (0.1 μg) selectively and reversibly enhanced the attractiveness of whichever reward CS was that rat's prepotent cue. CeA DAMGO microinjections made rats more vigorously approach their particular prepotent CS and to energetically sniff and nibble it in a nearly frenzied consummatory manner. Only the prepotent cue was enhanced as an incentive target, and alternative cues were not enhanced. Conversely, inactivation of CeA by muscimol microinjection (0.25 μg) suppressed approach, nibbles, and sniffs of the prepotent CS. Confirming modulation of incentive salience, unconditioned food intake was similarly increased by DAMGO microinjection and decreased by muscimol in CeA. We conclude that opioid neurotransmission in CeA helps determine which environmental stimuli become most “wanted,” and how “wanted” they become. This may powerfully guide reward-seeking behavior.